Immediate Effect of Passive Smoking on Microcirculatory Flow. (October 2014) - Henriksson, Peter; Lu, Qing; Diczfalusy, Ulf; Freyschuss, Anna
Abstract Objective Exposure to SHS, as by passive smoking, seems to increase the incidence of cardiovascular events. It has been shown that active smoking of a single cigarette causes an immediate and significant decrease in microcirculatory blood flow velocity, whereas the acute effects of exposure to SHS on microcirculatory flow have as yet not been demonstrated. Methods Healthy nonsmoking volunteers of both genders were studied during acute exposure to SHS of two cigarettes burning up to 10 minutes. Microvessels were examined by in vivo vital capillaroscopy (Capiflow®), allowing continuous assessment of CBV. Results CBV decreased from 514 mm/sec (CI 383–646) at baseline to 306 mm/sec (CI 191–420) at end of SHS exposure with a further decrease to a nadir of 240 mm/sec (CI 155–325) four minutes after the end of this exposure (p < 0.0001; ANOVA). Conclusions The result of this study shows that passive inhalation of secondhand cigarette smoke induces an immediate and prolonged marked reduction in CBV in nonsmoking healthy volunteers.